Forest Fire Potential in KPH Bogor Perum Perhutani Unit III West Java and Banten POTENSI KEBAKARAN HUTAN DI KPH BOGOR PERUM PERHUTANI UNIT III JAWA BARAT DAN BANTEN - Bambang Hero Saharjo; Fildah Amalina (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2016)
Forest fire potential can be studied through forest fire control mechanism and the source of it naturally based and human activity. The aims of the research are to analyze the level of vulnerability forest fire based on the rainfall recorded during the last 5 years in order to study the source of forest fire and the efforts that had been established on forest fire controlling by KPH Bogor. The result of research shown that the average of annually rainfall rate was 2 545 mm. It can be categorized into not prone toward forest fire. The other potential of forest fire was through land clearing that was low because it was controlled and applied by the society. Meanwhile the big potential of forest fire occurred was caused by social conflict due to the lack of good relationship between KPH Bogor and the society. Lack nformation about socialization program and attention toward the existence of warning board is a ineffective forest fire controlling.Keywords: forest fire controlling, forest fire potential, human activity, KPH Bogor, rainfall